Corpus of Interviews with Adult Learners of Scots (COIALS) - Linda Bruce (21587978) (2025)
A dataset consisting of a corpus of interviews with adult learners of Scots (COIALS). 217,887 word corpus compiled from 25 semi-structured qualitative interviews with adult learners of Scots in Scotland. Interviews took place between August 2022 and August 2023. Research received a favourable opinion from the Open University Human Research and Ethics Committee: HREC reference HRE/4543/Bruce. Supporting documents: COIALS readme file, COIALS User Manual, 'whole corpus' (25 interviews transcribed and saved as a plain text file), Metadata file providing information on participants and interviews, transcription conventions and Scots word list, list of 'find and replace' rules used for implementing POS and lemma tags for the Scots language.